A critical review of professional satisfaction theories in nursing - Papathanassoglou, Elizabeth; Lemonidou, Chryssoula; Karanikola, Maria (My University, 2007)
Background: Associations between the lack of professional satisfaction among nurses and phenomena with a negative impact on the quality and safety of nursing care, such as professional burn-out and intention to leave, have been reported in several studies. Purpose: The purpose of the present study was to critically review and to compare current theoretical frameworks and models of professional satisfaction in nursing, along with the pertinent research evidence. Method: A critical narrative review was carried out. Evidence was collected through the MEDLINE and CINHALL databases and the US National Library of Medicine. Books and published studies from 1985 to January 2007 were selected according to pre-specified criteria. Findings: Multiple theoretical frameworks and models on professional satisfaction have been constructed, some of which have been supported by appropriate empirical evidence. Nonetheless, based on research evidence and theoretical premises, the organization and empowerment theories may be viewed as the most pertinent and up to date frameworks for the study of professional satisfaction in nursing, since they have been constructed for nursing specifically, and they take into account the unique political, organizational and social circumstances of the profession.
Κριτική ανασκόπηση των θεωριών επαγγελματικής ικανοποίησης στη νοσηλευτική
Keywords: Satisfaction; Professional satisfaction; Nursing personnel